2016
DOI: 10.1080/14330237.2016.1163894
|View full text |Cite
|
Sign up to set email alerts
|

Vicarious trauma: The psychological impact of working with survivors of trauma for South African psychologists

Abstract: Traumatic events are highly prevalent in South African society and psychologists who work with survivors of trauma have been identified as particularly at risk of being adversely affected by their work, and experiencing vicarious trauma. This study aimed to explore the experiences of a group of South African psychologists who work predominantly with trauma survivors. Individual semi-structured interviews were conducted with six psychologists (females = 67%). The predominant type of trauma encountered by partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
61
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(72 citation statements)
references
References 34 publications
4
61
0
1
Order By: Relevance
“…As STS or VT research with trainees is in its infancy, it would be premature to entirely discount the existence of VT among trainees. It may be useful to explore disrupted beliefs within qualitative research as this may facilitate the development of perhaps more appropriate or sensitive VT measures, because Sabin‐Farrell (), Fucci (), and Sui and Padmanabhanunni () found some qualitative evidence of cognitive changes consistent with the VT model. Indeed in their metasynthesis of 20 qualitative studies on VT and vicarious posttraumatic growth, Cohen and Collens () identified a theme involving changes in beliefs within the studies they reviewed.…”
Section: Discussionmentioning
confidence: 99%
“…As STS or VT research with trainees is in its infancy, it would be premature to entirely discount the existence of VT among trainees. It may be useful to explore disrupted beliefs within qualitative research as this may facilitate the development of perhaps more appropriate or sensitive VT measures, because Sabin‐Farrell (), Fucci (), and Sui and Padmanabhanunni () found some qualitative evidence of cognitive changes consistent with the VT model. Indeed in their metasynthesis of 20 qualitative studies on VT and vicarious posttraumatic growth, Cohen and Collens () identified a theme involving changes in beliefs within the studies they reviewed.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in other developing countries (Uganda: Ager et al, 2012; India: Shah et al, 2007) have confirmed that lay counsellors in these settings are particularly vulnerable to STS and burnout as a consequence of their work. Nevertheless, the vast majority of South African research in this area has focused on the experiences of professionals including psychologists (Sui & Padmanabhanunni, 2016), nurses (Mashego et al, 2016), and social workers (MacRitchie & Leibowitz, 2010).…”
mentioning
confidence: 99%
“…Several psychological treatments for PTSD have been developed over the last four decades [7]. Yet health professionals, such as clinical psychologists, are still at risk psychologically when treating persons with PTSD [1,8]. Treating PTSD is understood to be demanding as it requires re-tellings of the trauma narrative using various psychotherapies, such as cognitive behavioural therapy [9].…”
Section: Introductionmentioning
confidence: 99%
“…Treating PTSD is understood to be demanding as it requires re-tellings of the trauma narrative using various psychotherapies, such as cognitive behavioural therapy [9]. However, listening to the details of patients' trauma narratives exposes practitioners to traumatic stress, vicarious trauma and secondary trauma [8,10].…”
Section: Introductionmentioning
confidence: 99%